2021
DOI: 10.2147/ppa.s301644
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Treating “OFF” Episodes in Parkinson’s Disease: A Discrete Choice Experiment

Abstract: Introduction Several on-demand treatments are available for management of “OFF” episodes in patients with Parkinson’s disease (PD). We evaluated patients’ preferences for features of theoretical on-demand treatment options. Methods In a discrete choice experiment, US adults with self-reported PD of ≥5 years, or <5 years with “OFF” episodes, taking oral carbidopa/levodopa, selected between pairs of theoretical on-demand treatments that varied by mode of administration (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Although the TPQ was developed for this study and has not been formally validated, alignment between the TPQ and TSQM findings supports the content validity of the TPQ. These results align with a previous finding that, for OFF treatment modes associated with AEs, patients with PD reported a preference for a hypothetical sublingual film associated with mouth/lip sores versus a hypothetical injectable medication associated with injection site reactions [29]. Further, an indirect treatment comparison based on a systematic literature review suggested that SL-APO and SC-APO are comparable in efficacy but additional factors, including mode of administration, may influence treatment decisions [30].…”
Section: Discussionsupporting
confidence: 88%
“…Although the TPQ was developed for this study and has not been formally validated, alignment between the TPQ and TSQM findings supports the content validity of the TPQ. These results align with a previous finding that, for OFF treatment modes associated with AEs, patients with PD reported a preference for a hypothetical sublingual film associated with mouth/lip sores versus a hypothetical injectable medication associated with injection site reactions [29]. Further, an indirect treatment comparison based on a systematic literature review suggested that SL-APO and SC-APO are comparable in efficacy but additional factors, including mode of administration, may influence treatment decisions [30].…”
Section: Discussionsupporting
confidence: 88%
“… 23 A DCE survey to evaluate patient preferences for attributes of on-demand therapies for OFF time—including mode of administration (with associated AEs), time to and duration of ON time, and out-of-pocket cost—found that patients prioritize cost, mode of administration with associated AEs, and time to ON time more than they do duration of ON time. 24 Our results are broadly consistent with prior studies in demonstrating that, while optimizing ON time is a priority for individuals with PD, AEs and risks associated with PD treatments are key drivers of preferences.…”
Section: Discussionsupporting
confidence: 90%
“…Among them, "institutional scale" and "waiting time for hospital admission" were subdivided from the behavioral model of health services use proposed by Andersen (20,22). Additionally, since patients generally value the economic accessibility and spatial convenience of health-seeking behavior, for example, the out-of-pocket cost for a 30-day supply (12), service price (23), and travel time were veri ed in empirical study; and thus "time from residence to hospital" and "out-of-pocket expenses per time" were included in the attribute list. Moreover, considering the nature of China's nepotistic society in which people want to use "relationships" to gain convenience in normal procedures, the attribute of "hospital with or without acquaintances" was considered.…”
Section: Determination Of Attributes and Levelsmentioning
confidence: 99%
“…Furthermore, in the research eld of patients' health preferences, the analysis methods routinely used include multivariate analysis(16), logistic regression analysis (17), cross analysis(18), etc., which do not pay attention to the fact that patients' inpatient preference is the result of combinations of multiple factors and that the importance of different factors varies. In recent years, discrete choice experiment (DCE) has been put into use in the research eld of patient preference (12,15). DCE is based on random utility theory assuming that respondents always prefer the alternative that offers the greatest utility, and its overall utility is decomposed by its attributes (19).…”
Section: Introductionmentioning
confidence: 99%